The peculiarities of hulled barley in the evaluation of its productivity and quality of grain (review) - O. L. Tsandekova; O. A. Neverova (Зерновое хозяйство России)
The review presents the results of the comparative evaluation of physical and biological characteristics of hulled and unhulled varieties of barley. The work shows the advantages of the hulled lines of barley in comparison with unhulled varieties in protein accumulation, amino-acid content and oil. The advantages of the hulled early-maturing barley samples compared to the middle-maturing samples have been established as they produce the largest indexes of such essential amino acids as lysine, phenylalanine, methionine and threonine, as well as the largest number of such fatty acids as linoleic and linolenic. The various approaches to improve productivity and quality of hulled barley with the help of biochemical indexes have been considered that is of great theoretical and practical value. The article considers different studies of physiological peculiarities of hulled barley and mechanisms of its stability. The authors discuss the perspectives of the use of such physical and biochemical indexes as the number of photosynthetic pigments, the intensity of photosynthesis, morphometric characteristics (leaf area, mass of dry plant) in plant-breeding to estimate the initial material and to select highly productive forms of hulled barley as the test indexes for the improvement of productivity and quality of grain.